Policy Reformulation Action-Cycle Framework (PRACYF): A Case Study Decentralization and Regional Autonomy Policy in North Sumatra Province - Gunawan Undang; Heri Heri; Deden Suhendar; Eny Nuryani R; Achdijat Sulaeman; Meiry Akmara Dhina; Adam Darmawan (Jurnal Manajemen Pelayanan Publik, 2023)
Decentralization and regional autonomy (DRA) policies have been implemented in Indonesia for 25 years. However, regional independence is still very low in 33 regions/cities in North Sumatra (North Sumatra) because the local revenue (PAD) is much smaller than the regional income and expenditure budget (APBD). The aim of this study is to analyze this phenomenon and find a conceptual framework for reformulating DRA policies. The research method uses mixed methods. The results of the analysis show that 88.49% of the regions are still dependent on transfer funds from the central government, so the nature of autonomy, namely the independence of autonomous regions, is still far from expectations. In the long run, it is important to reformulate policies through the Policy Reformulation Action-Cycle Framework (PRACYF). Theoretically, PRACYF has conceptual implications for the development of public policy and DRA, while in practice it can have implications for increasing the independence of autonomous regions and the welfare of the people in the regions.